NATO: The Next Thirty Years - Myers, Kenneth A. (Boulder Westview Press, Inc, 1980)
The survival of NATO as a viable alliance is currently challenged by a shift in the strategic balance of power as well as by global events and contingencies that extend far beyond NATOs boundaries. In the face of these challenges, existing institutional mechanisms are proving inadequate for an effective response.
Keywords: Army